A unified index for power quality evaluation in distributed generation systems. (15th April 2018) - Elbasuony, Ghada S.; Abdel Aleem, Shady H.E.; Ibrahim, Ahmed M.; Sharaf, Adel M.
Abstract: Excessive penetration of distributed generation units with their electronic power interfaces into distribution systems has introduced different power quality problems into these systems. To date, there is no agreed upon approach to quantify the overall power quality performance of a system in the presence of distributed generation units. In this paper, a unified index for power quality assessment in different distributed generation systems is proposed using the analytic hierarchy process. The unified index is determined in terms of six power quality performance parameters, namely voltage total harmonic distortion, current total harmonic distortion, frequency deviation, voltage sags score, voltage flicker, and power factor at different interface buses of three grid-connected distributed generation systems: distributed wind, wind/photovoltaic, and hybrid wind/photovoltaic/fuel cell energy systems. Simulations are carried out in the Matlab-Simulink environment. The results show that the proposed index can facilitate overall power quality evaluation of different systems under different operating conditions. It makes the assessment simple and effective as one number only is used for each comparison. Furthermore, based on the values of the index in the different systems, it was found that the hybrid energy system shows better power quality performance compared to the other systems. Highlights: Power quality assessment in different distributed generation systems is proposed. Distributed generation systems with different interface configurations are considered. Analytic hierarchy process is used to determine the unified power quality index. The higher the value of the index, the lower is the system power quality. Hybrid distributed generation systems show better power quality performance.